penerapan Penerapan Keadilan Restoratif Dalam Penanganan Tindak Pidana Guna Mewujudkan Kemanfaatan dan Keadilan Masyarakat Tahun 2022: Penerapan Keadilan Restoratif Dalam Penanganan Tindak Pidana Guna Mewujudkan Kemanfaatan dan Keadilan Masyarakat Tahun 2022 - Azis Saputra (Pusat Penelitian dan Pengembangan Polri, 2023)
Law is essentially a system of human life in society and state. In the criminal criminal system, the police institution is a state instrument that plays a role in maintaining security and protecting the community, enforcing the law, and providing protection, protection and services to the community in order to maintain domestic security. The effect of the criminal criminal process on the sense of justice and the benefits of law for the community in handling cases is not yet optimal, which has encouraged law enforcement agencies, especially the police, to look for alternative case resolution solutions to the existing criminal criminal system by resolving cases outside of court, the method in question is by means of mediation as entertainment from restorative justice so that it is necessary to think about resolving criminal cases through the Alternative Dispute Resolution route (ADR. The National Police Research and Development Center carried out this research using a qualitative approach and secondary data collection. Respondents and informants consisted of internal and external Polri. Internal Polri consisted of Regional Police Officers , Polres, as well as related Polres members. Externally, the Polri are Community Leaders, Religious Leaders, Traditional Leaders, Youth Leaders, Government Agencies (Kesbangpol), and NGOs/Ormas. The results of the research state that: the implementation of restorative justice requires socialization of Perpol Number 8 2021 concerning Restorative Justice; coordination between functions has not been implemented optimally because cross-functional knowledge transfer has not occurred; cross-functional and stakeholder coordination activities need to be optimized; training in the ability to detect, identify and solve security and community welfare problems must be carried out on an ongoing basis; Technical direction is needed to emphasize that investigators are not directly involved in the peace process between the perpetrator and the victim; The need to increase publication of criminal handling based on restorative justice; It is necessary to regulate the time limit for the process from investigation to fingerprints to speed up the restorative justice process.